Phosphodiesterase 7: a potential novel therapeutic target in ovarian cancer - Tessarollo, Nayara Gusmão; Guimarães, Isabella dos Santos; dos Santos, Diandra Zipinotti; Henriques, Taciane Barbosa; Lyra-Junior, Paulo Cilas Morais; Carlos de Souza, Josiany; Pimenta, Tatiana Massariol; Martins, Bárbara da Silva; Butzene, Solenny Maria Silva; Padilha, José Matheus Simões; Maciel, Leide Laura Figueiredo; Almeida, João Carlos de Aquino; et al. (Frontiers in Pharmacology, 2025)
IntroductionChemoresistance and disease relapses in epithelial ovarian cancer (EOC) highlight the need for novel therapeutic strategies. Here, we investigated phosphodiesterase 7A (PDE7A) as a potential target in ovarian cancer treatment.MethodsGene expression was performed by RNA sequencing data comparing high-grade serous ovarian carcinoma (HGSOC) and fallopian tube samples. The PDE7 inhibitor BRL 50481, alone or combined with paclitaxel (PTX), was tested in drug-sensitive A2780 and multi-resistant OVCAR3 cells by Diphenyltetrazolium bromide (MTT) assay. To validate data from the high throughput RNA-sequencing assays, RT-qPCR and Immunoblotting were performed. Cytokine expression was analyzed by RT-qPCR and the quantification was obtained by ELISA. Scanning and Transmission Electron Microscopy were also carried out.Results and discussionMTT assays revealed that while BRL 50481 reduced metabolic cellular viability (MCV) in A2780 (IC50 = 200 μM), its combination with PTX decreased MCV in both lines, reducing PTX IC50 by 103- and 625-fold in A2780 and OVCAR3, respectively. PDE7 inhibition suppressed the PI3K/AKT/mTOR pathway, upregulated the pro-apoptotic protein Bcl-2 Associated X-protein (BAX) in A2780, and increased IL-6 expression in OVCAR3. Pretreatment with BRL 50481 followed by PTX downregulated vimentin and octamer-binding transcription factor (OCT4), while inducing morphological changes and mitochondrial cristae alterations. Inhibiting PDE7 can enhance the paclitaxel-induced apoptosis by promoting mitochondrial dysfunction and suppressing survival pathways, thereby improving ovarian cancer treatment efficacy. The results need to be validated in additional in vivo models.